Analysis of Renewable Energy Directive Ii on Trading of Indonesian Palm Oil Associated with GATT - Amanda Fadhilla Chairunisa; Imam Haryanto (Yuridika, 2021)
International economic relations sure is very important for a country and the important thing that follows is the policy that regulates international economic relations it self. In this study, the authors will analyze hows  Renewable Energy Directive II (RED II) policy as a derivative of the RED (Renewable Energy Directive) policy by the European Union will affect the Indonesian palm oil trade which this also would show the violations of previous policies that is General Agreement on Tarifs and Trades. Authors also going to show General Agreement on Tariffs and Trade (GATT) as a policy that regulates how international trade relations should be carried out and the violations of this international agreement undoubtedly could affect Economic relations between the two countries, both on a micro scale and macro scale. In conducting the research authors will be using the normative juridical methods which means the legal research will be based off library materials and secondary materials therefore the main result from this study would be a reflection of how RED II can affect trade in indonesian palm oil products and also by effecting this regulation in 2021 the european union will be violating the non-discrimination principle in GATT 1947.